Digestive polyposis: Round table XXVI Uruguayan Congress of Surgery: coordinator Manuel Albo - Albo, Manuel; Falconi, Luis M; Trostchansky, José; Sarroca, Carlos; Castiglioni Barriere, Juan Carlos; Viola Núñez, Humberto (Cirugía del Uruguay, 1976)
This Table will deal with digestive polyps and polyposis located topographically from the cardia to the anus. Upper digestive tract lcs are therefore excluded. which are generally beyond the domain of the general surgeon.